Determinants of business performance in Ecuador during the COVID-19 pandemic - Ríos, David (2021)
The COVID-19 crisis hit the national economy in a negative and unexpected way because, in an attempt to preserve the health of Ecuadorians, the Government took preventive actions to avoid contagion of this disease, such as: suspension of economic activities and the confinement of the first months (March and April 2020) of the crisis. This caused a decrease in the country's domestic demand, since in the second quarter of 2020 there was a decrease of 12% compared to the previous quarter, which undoubtedly affected the supply sector since it contracted by approximately 13% ( Central Bank of Ecuador, 2020b), including in the latter, businesses and / or enterprises of the different sectors of the country's economy and weakening the business apparatus of Ecuador.Despite the fact that in the first months of pandemics (March, April, May) there were high unemployment rates and little creation of new companies (ECB, 2020a; Superintendency of Companies, 2021), these figures have improved inferring that the business apparatus of the economy is in the process of reactivation. In this way, the objective of this research is to identify, based on the pre-existing literary review, the factors that influence the performance of companies in this context of crisis, to contribute to making the right decisions in the business sector of Ecuador.